Soft tissue regeneration using leukocyte-platelet rich fibrin after exeresis of hyperplastic gingival lesions: two case reports. (December 2015) - di Lauro, A.E.; Abbate, D.; Dell'Angelo, B.; Iannaccone, G.A.; Scotto, F.; Sammartino, G.
Abstract Introduction Leukocyte-platelet rich fibrin belongs to a second generation of platelet concentrates that does not need biochemical blood manipulation. It is used for tissue healing and regeneration in periodontal and oral-maxillofacial surgery. We report two cases of hyperplastic gingival lesions treated by exeresis and application of leukocyte-platelet rich fibrin membranes in order to improve and accelerate tissue healing. Case presentation Two patients (a 78-year-old Caucasian woman and a 30-year-old Caucasian man) were treated for hyperplastic gingival lesions. They underwent to exeresis of lesions and application of leukocyte-platelet rich fibrin membranes. Tissue healing was clinically evaluated after 1, 3, 7, 14 and 30 postoperative days. No recurrences were observed after 2 years of semi-annual follow up. Conclusions We obtained rapid and good healing of soft tissues probably due to the elevated content of leukocytes, platelets and growth factors in the leukocyte-platelet rich fibrin. Based on our results we suggest the use of leukocyte-platelet rich fibrin to cover wounds after exeresis of oral neoformations such as hyperplastic gingival lesions.